Pengembangan Rencana Pelaksanaan Pembelajaran Matematika Kurikulum 2013 Berbasis Lesson Study Pada Siswa Kelas VIII SMP Negeri 1 Salatiga Tahun 2015/2016 - Hidayati, Wahyu Nur, Prof. Dr. Sutama,M.Pd (2016)
Lerning Implementation Plan (RPP) was important, because it is a reference for teachers to implement learning activities in order to be more focused and systematic. The purpose of this research and development is (1) To analyze and descripe the preparation of RPP math teachers do curriculum 2013 in SMP Negeri 1 Salatiga. (2) To compile the development of mathematics based lesson study. (3) To analyze and test the feasibility of a mathematical lesson plans developed based esson study. This type of the research and development is a R&D research. The observation time of this research is in the second semester of the 2015/2016 academic year. The subjects were teacher of SMP Negeri 1 Salatiga. Technique of collecting data are using questionnaires, interviews, and documentation. The data collected are analyzed by using three grooves methods and . The validity of the data n this research is using triangulation resources and techniques. The result of the study states (1) preparations of RPP mathematics curriculum 2013 SMP Negeri 1 Salatiga components and principle pursuart to Rule Minister of Education and Culture of the Republic of Indonesia number 65 of 2013 on Standart for primary and secondary education process. 2) RPP development of mathematics curriculum based lesson study in 2013 obtained the result of all validators which amounted to 6 experts claim feasible and validation RPP shows the total score is 468 so that the end product of research in the form of RPP has met eligibility. (3) Learning Implementaton Plan (RPP) based mathematics lesson study developed eligible for use in the learning of mathematics SMP. Keywords: lesson study, lesson plan, curriculum 2013, mathematics